A protocol for scoping reviews on the role of whole-body and dedicated body-part magnetic resonance imaging for assessment of adult and juvenile idiopathic inflammatory myopathies - Essouma, Mickael; de Araujo, Daniel Brito; Day, Jessica; Conticini, Edoardo; Riopel, Mary Anne; Elias, Adriana Maluf; Paula, Vitor Tavares; Omori, Clarissa Harumi; Guimarães, Julio Brandão; Gibson, Daren; Saad-Magalhaes, Claudia [UNESP]; Appenzeller, Simone; et al. (Springer Nature, 2024)
Currently, standardized magnetic resonance imaging (MRI) scoring systems and protocols for assessment of idiopathic inflammatory myopathies (IIMs) in children and adults are lacking. Therefore, we will perform a scoping review of the literature to collate and evaluate the existing semi-quantitative and quantitative MRI scoring systems and protocols for the assessment and monitoring of skeletal muscle involvement in patients with IIMs. The aim is to compile evidence-based information that will facilitate the future development of a universal standardized MRI scoring system for both research and clinical applications in IIM. A systematic search of electronic databases (PubMed, EMBASE, and Cochrane) will be undertaken to identify relevant articles published between January 2000 and October 2023. Data will be synthesized narratively. This scoping review seeks to comprehensively summarize and evaluate the evidence on the scanning protocols and scoring systems used in the assessment of diagnosis, disease activity, and damage using skeletal muscle MRI in IIMs. The results will allow the development of consensus recommendations for clinical practice and enable the standardization of research methods for the MRI assessment of skeletal muscle changes in patients with IIMs.
Keywords: Assessment; Damage; Idiopathic inflammatory myopathy; Magnetic resonance imaging; Myositis